2021
DOI: 10.1111/1755-0998.13406
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of assembly strategies and quality metrics on the accuracy of the rewarewa (Knightia excelsa) genome

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…However, based on de novo assembly, we obtained a genome size of 1.71 Gb for the whitespot parrotfish. This variation in genome size may be due to changes in the quality and depth of sequencing data or assembly strategies [68,69]. Among them, we found that the whitespot parrotfish exhibited higher heterozygosity compared to C. undulatus [70].…”
Section: Genome Assembly and Annotationmentioning
confidence: 89%
“…However, based on de novo assembly, we obtained a genome size of 1.71 Gb for the whitespot parrotfish. This variation in genome size may be due to changes in the quality and depth of sequencing data or assembly strategies [68,69]. Among them, we found that the whitespot parrotfish exhibited higher heterozygosity compared to C. undulatus [70].…”
Section: Genome Assembly and Annotationmentioning
confidence: 89%
“…69 Genomics of other members of the Proteaceae is progressing with the sequencing of the Waratah (Telopea speciosissima) supported by the Genomics of Australian Plants Program of Bioplatforms Australia (https:// www.genomicsforaustralianplants.com/) and the Nightcap Oak (Eidothea hardenianna) supported by the Threatened Species Initiative and Rewarewa (Knightia excelsa) in New Zealand. 70 These species are of value as ornamentals or for timber and the analysis of their genomes will advance knowledge of the evolution and biology of the Proteaceae. Other Proteaceae species with seeds that have been considered food sources include Hicksbeachia pinnatifolia and Athertonia diversifolia.…”
Section: Macadamiamentioning
confidence: 99%
“…In addition, the chromosomal assembly pipelines is inconsistent in different studies 27,28 and lack a well-tested, standardized workflow. Moreover, some critical steps such as removing haplotig, organelle DNA contamination and gap closing are prone to being overlooked 32,33,34 . Given that only 0.17% of the eukaryotic species have undergone genome assembly 5 , there is a great need for a standardized and user-friendly automated tool for accurate chromosome-level genome assembly.…”
mentioning
confidence: 99%